(3GdNdGUI GdGcJSGHjI aj GdCdZGR GdMSGHjIs - (3haGFj GdMcje , MSjf haGFj Hf MSf GdHZOGOj,J (B1336 (3g` s
(3ChdgG (B:s
,(3HYO ajbhd haGFi Hf GdeQMhe GdTjN MSjf GdHZOGOi gPg QSGdI SfjI hYLGdI HgjI eTJedI Ydi NeSjf aiGdeSGFd GdMSGHjI s
(3BNQgG (B:s
(3Ef GUd GdeGd (B32 (3Lfjg hgh GdeWdhH s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B261s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(4055 (3c(B) s
Keywords: (3GdQjGVjGJs